Programmed cell death in Saccharomyces cerevisiae is hampered by the deletion of GUP1 gene - Tulha Joana; Faria-Oliveira Fábio; Lucas Cândida; Ferreira Célia (BMC Microbiology, 2012)
Abstract Background During the past years, yeast has been successfully established as a model to study mechanisms of programmed cell death regulation. Saccharomyces cerevisiae commits to cell death showing typical hallmarks of metazoan apoptosis, in response to different stimuli. Gup1p, an O-acyltransferase, is required for several cellular processes that are related to apoptosis development, such as rafts integrity and stability, lipid metabolism including GPI anchor correct remodeling, proper mitochondrial and vacuole function, bud site selection and actin dynamics. Therefore, we hypothesize that apoptotic process would be affected by GUP1 deletion. Results In the present work we used two known apoptosis inducing conditions, chronological aging and acetic acid, to assess several apoptotic markers in gup1∆ mutant strain. We found that this mutant presents a significantly reduced chronological lifespan as compared to Wt and it is also highly sensitive to acetic acid treatment. In addition, it presents extremely high levels of ROS. There were notorious differences on apoptotic markers between Wt and gup1∆ mutant strains, namely on the maintenance of plasma membrane integrity, on the phosphatidylserine externalization, on the depolarization of mitochondrial membrane and on the chromatin condensation. Those suggested that the mutant, under either condition, probably dies of necrosis and not from apoptosis. Conclusions To Gup1p has been assigned an important function on lipid rafts assembly/integrity, lipid metabolism and GPI anchor remodeling. Our results provide, for the first time, the connection of the integrity of yeast lipid rafts and apoptosis induction and/or signaling, giving new insights into the molecular mechanisms underlying this process in yeast.